Design of Hydrophilic Metal Organic Framework Water Adsorbents for Heat Reallocation. (20th July 2015) - Cadiau, Amandine; Lee, Ji Sun; Damasceno Borges, Daiane; Fabry, Paul; Devic, Thomas; Wharmby, Michael T.; Martineau, Charlotte; Foucher, Damien; Taulelle, Francis; Jun, Chul‐Ho; Hwang, Young Kyu; Stock, Norbert; et al.
<x xml:space="preserve">Abstract</x> A new hydrothermally stable Al polycarboxylate metal–organic framework (MOF) based on a heteroatom bio‐derived aromatic spacer is designed through a template‐free green synthesis process. It appears that in some test conditions this MOF outperforms the heat reallocation performances of commercial SAPO‐34.